2015
DOI: 10.3109/00365521.2015.1010571
|View full text |Cite
|
Sign up to set email alerts
|

Screening for celiac disease in Danish adults

Abstract: Objective. The prevalence of celiac disease (CD) as recorded in the Danish National Patient Registry is ∼50/100,000 persons. This is much lower than the reported prevalence of CD in other Nordic countries and underdiagnosis is suspected. Our aim was to estimate the prevalence of CD in a population-based study of Danish adults. Methods. A total of 2297 adults aged 24–76 years living in the southwestern part of Copenhagen were screened for CD by immunoglobulin (Ig)A and IgG antibodies to transglutaminases and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 32 publications
4
42
0
3
Order By: Relevance
“…The screening for CD has been described elsewhere. 15,17 A total of 3405 participants were eligible for invitation and 2308 individuals (54.2% female) were re-examined. The mean age at the five-year-follow-up examination was 55.7 years (range: 24-76 years).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The screening for CD has been described elsewhere. 15,17 A total of 3405 participants were eligible for invitation and 2308 individuals (54.2% female) were re-examined. The mean age at the five-year-follow-up examination was 55.7 years (range: 24-76 years).…”
Section: Study Populationmentioning
confidence: 99%
“…[12][13][14] We have conducted a screening for CD in a general Danish population. 15 In a further analysis of this cohort we aimed to map the distribution of HLA DQ2 and HLA DQ8 haplotypes and examine their association with CD and other diseases, symptoms and biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…A population‐based study of CD in northern Sweden found a prevalence of 0.53%, and a study in Denmark supports earlier evidence, indicating a similar prevalence in the Scandinavian countries (Horwitz et al., 2015; Ivarsson et al., 1999; Sjoberg & Eriksson, 1999). More extensive screening methods point to a prevalence in many western countries approaching 1% (Green & Cellier, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Participants were further invited for a follow-up examination 5 years later, where parts of the baseline study examination were repeated. 24,25 Eligible criteria for our study were a full set of blood pressure (BP) measurements, data about use of antihypertensive medication, and baseline ultrasound measurements of SAT and VAT. Exclusion criteria were prevalent CVD at baseline.…”
Section: Study Populationmentioning
confidence: 99%